Southern Pines Are Resistant to Mortality From an Exceptional Drought in East Texas - Klockow, Paul A.; Edgar, Christopher B.; Moore, Georgianne W.; Vogel, Jason G. (Frontiers in Forests and Global Change, 2020)
In 2011, the state of Texas experienced its worst drought ever recorded, breaking statewide temperature and precipitation records. With climate predictions suggesting increases in the severity and extent of future droughts in this region, forest managers will need to plan for such events to minimize tree mortality. In east Texas, pine species are economically and ecologically important and are often managed, providing an opportunity to examine silvicultural strategies for mitigating exceptional drought mortality. We used U.S. Forest Service Forest Inventory and Analysis data and Bayesian, logistic, mixed effects regression to model individual tree mortality and the effect of stand structure (i.e., tree size, relative density, and species dominance) on three major pine groups, planted (PL) and naturally-regenerated (NL) loblolly pine (Pinus taeda L.) and all shortleaf pine (SL, Pinus echinata Mill.), under pre-drought and drought periods in east Texas. These groups represent a spectrum of management intensity with PL generally intensively managed and NL and SL relatively unmanaged. Moreover, loblolly pine tends to be production-oriented while shortleaf pine has perceived drought tolerance. Surprisingly, pine mortality did not increase significantly from pre-drought to drought periods in spite of the record drought conditions. However, mortality differed between pine groups and in response to stand structure for loblolly pine. Planted loblolly was least affected as mortality rate increased 9.8%. In contrast, NL and SL pine mortality rates were significantly higher than PL and increased 26.3% and 20.0%, respectively. The smallest and largest stems experienced elevated mortality under both periods, notably PL under exceptional drought. As expected, higher densities of loblolly pine exacerbated exceptional drought mortality. Surprisingly, greater overstory diversity for NL reduced mortality under exceptional drought. Despite the unprecedented hot and dry conditions of the 2011 drought, our results suggest that current practices in PL that manage relative density and tree size for non-drought conditions confers mortality resistance under exceptional drought. In NL stands, mortality resistance could be increased through active thinning and promoting greater overstory diversity. These results offer critical knowledge for managers tasked with providing continued forest resources in the face of future exceptional droughts.